2017
DOI: 10.1111/are.13296
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance of juvenile freshwater prawnsMacrobrachium rosenbergiiin biofloc system

Abstract: The aim of this study was to compare two rearing systems for freshwater prawn Macrobrachium rosenbergii: one with use of a recirculating aquaculture system with biofilters (RAS) and another with use of microbial flocs (F). Thirty postlarvae of freshwater prawn with an initial average weight of 0.13 AE 0.05 g were randomly stocked in six experimental units with 0.20 m² and volume of 50 L. The experiment lasted thirty days. Dissolved oxygen, temperature and pH were monitored daily; ammonia concentration was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
(27 reference statements)
3
31
1
Order By: Relevance
“…On the other hand, Burford et al (2004) observed a range between 18 and 29% of nitrogen consumed by Pacific white shrimp originated from BFT. Furthermore, according to Ballester et al (2017), the bacterial communities that make up the bioflocs may provide better responses for disease resistance and survival, which can explain the superior S (87%) in BFT in comparison to RAS (79%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Burford et al (2004) observed a range between 18 and 29% of nitrogen consumed by Pacific white shrimp originated from BFT. Furthermore, according to Ballester et al (2017), the bacterial communities that make up the bioflocs may provide better responses for disease resistance and survival, which can explain the superior S (87%) in BFT in comparison to RAS (79%).…”
Section: Discussionmentioning
confidence: 99%
“…The RAS experimental tanks (useful volume of 150 L) were composed by independent recirculation system and supplementary aeration via radial air blower (1 hp/system). Air-lift biofilters (10 L) were used in RAS, according to recommendations of Ballester et al (2017). The thermostats coupled to shielded resistance (500 W/tank) were used to keep the water temperature constant at 26.0°C.…”
Section: Experimental Systemmentioning
confidence: 99%
“…Lower prevalence of infection has been associated with lower salinity culture conditions,and use of biofloc systems and lined ponds (Gabaudan, 2012;NACA, 2012;De Schryver et al, 2014;Boonyawiwat et al, 2017). Juvenile shrimp, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The use of biofloc can increase feed utilization, growth, survival and the reproductive performance of cultured animals (Xu et al, 2012;Ekasari et al, 2014;Suita, 2016;Ballester et al, 2017). Moreover, some studies have investigated the beneficial immunological effects of the organisms found in biofloc, and their cellular components and metabolites can act as immunostimulants to enhance the shrimp innate immune system and provide improved protection against pathogens (Vazquez et al, 2009;Crab et al, 2010;Ekasari et al, 2014;de Jesus Becerra-Dorame et al, 2014;Xu et al, 2014;Kim et al, 2014; in press a).…”
Section: Introductionmentioning
confidence: 99%
“…Among these benefits are greater growth and survival in cultured animals, a decrease in commercial food investment, improvement in water quality, and fewer water refills. Ballester et al (2017) cultivated prawns (M. rosenbergii) with two treatments, a biofilter recirculation system (RAS) and another with microbial flocs (F). Resulting in the high density of rotifers, ciliates, and flagellate, as well as bacteria, these were identified in treatment F, and attributed to the source of carbon used; because the carbon source promotes an increase in bacterial biomass, which, in turn, stimulates the development of other microorganisms, and these will be used as natural food in situ by cultured animals.…”
Section: Biofloc Systemmentioning
confidence: 99%